Optical spectroscopy studies of the interaction between thiophanate methyl and human serum albumin for biosensor applications - Yahia, I. S.; AI-Khedhairy, Abdulaziz A.; Musarrat, Javed; Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2011)
Optical properties of the interaction between thiophanate methyl and human serum albumin have been investigated for biosensor applications. The interaction between human serum albumin (HSA) and thiophanate methyl (MT) was investigated by UV-Vis absorption spectra and atomic force microscopy. The optical constants (refractive index, absorption index, band gap and dielectric properties) of HSA MT and MT+HSA films were determined using absorbance, transmittance and reflectance spectra. The refractive index dispersion curve (>530 nm) exhibits the normal dispersion. The refractive index of the MT+HSA is higher than both HSA and MT alone due to the highest reflectance of the mixture of MT and HSA. This behavior is indicative of the complex formation between the MT and HSA. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Biosensor; Human serum albumin (HSA); Thiophanate methyl (MT); Optical constants; AFM